Foliage and Fog: Uncanny Petrocultures in Tash Aw’s We, the Survivors and Helon Habila’s Oil on Water - Uy, Jamie (SARE: Southeast Asian Review of English, 2022)
EcoGothic studies has, so far, primarily focused on uncanny environments imagined by Western writers. In response, this article compares polluted, haunting environments in two contemporary Anglophone novels from the Global South: Tash Aw’s We, the Survivors(2019) and HelonHabila’s Oil on Water(2011). Through vivid representations of the forbidding jungles of Malaysian palm oil plantations and the toxic waters of the oil-rich Niger Delta, both novels render extractive economies palpable and monstrous. This essay analyses how dystopian atmospheres, fragmented first-person narration, and circular crime fictions contribute to the EcoGothic aesthetic in both novels. Re-focusing scholarly attention from the dark woods of Europe and North America to the decaying mangroves across Asia and Africa foregrounds the ruinous aftermath of Western imperialism and neoliberal capitalism. By examining uncanny environments in Aw and Habila’s novels, this essay sheds new light on the neglected EcoGothic effects of Global South petrofiction.